Effects of combined angiotensin II receptor antagonism and neprilysin inhibition in experimental pulmonary hypertension and right ventricular failure. (15th October 2019) - Andersen, Stine; Axelsen, Julie Birkmose; Ringgaard, Steffen; Nyengaard, Jens Randel; Hyldebrandt, Janus Adler; Bogaard, Harm Jan; de Man, Frances S.; Nielsen-Kudsk, Jens Erik; Andersen, Asger
Abstract: Background: Combined angiotensin II receptor antagonism and neprilysin inhibition by LCZ696 reduces morbidity and mortality in heart failure patients and works by reducing RAAS activity and increasing cGMP levels. This study aims to evaluate the effects of LCZ696 in rats with pulmonary hypertension and right ventricular (RV) failure. Methods: Pulmonary hypertension was induced in rats ( n  = 34) by combined exposure to the vascular endothelial growth factor-receptor antagonist SU5416 and hypoxia (SuHx). To distinguish pulmonary vascular from cardiac effects, isolated RV failure was induced by pulmonary trunk banding (PTB) in another group of rats ( n  = 40). In both models, the development of RV dysfunction was verified before randomization to treatment with LCZ696 (60 mg/kg/day) or vehicle for five weeks. Results: In the SuHx rats, LCZ696 treatment reduced the increase in RV pressure and the development of RV hypertrophy and RV dilatation compared with vehicle treatment. LCZ696 also reduced wall thickness of the smaller pulmonary arteries. In the PTB rats, LCZ696 treatment did not have any effects on RV hypertrophy or function. Conclusions: Combined angiotensin II receptor antagonism and neprilysin inhibition reduced RV systolic pressure, hypertrophy, and dilatation in rats with pulmonary hypertension. These effects seem secondary to pulmonary vascular changes, including reduced pulmonary vascular remodeling, as similar effects were not seen in rats with isolated RV failure. LCZ696 may have a therapeutic potential in the treatment of pulmonary hypertension. Highlights: LCZ696 improves morbidity and mortality in heart failure patients. In rats with PH and RV failure, LCZ696 reduced RV pressure and dilatation. These beneficial effects were not seen in rats with isolated RV failure. LCZ696 primarily works by pulmonary vascular and not direct RV effects. LCZ696 may be of interest in PAH patients and in heart failure patients with PH.